462 RELATIONSHIP BETWEEN PATIENT GENOTYPE, VENTRICULAR INVOLVEMENT AND SUDDEN CARDIAC DEATH IN PATIENTS WITH ARRHYTHMOGENIC CARDIOMYOPATHY. (15th December 2022) - Gueli, Ignazio; Alderotti, Bianca; Aimo, Alberto; Todiere, Giancarlo; Modena, Martina; Botto, Nicoletta; Vittorini, Simona; Vergaro, Giuseppe; Giannoni, Alberto; Passino, Claudio; Aquaro, Giovanni; Emdin, Michele; et al.
Abstract: Introduction: Arrhythmogenic cardiomyopathy (AC) is an important cause of sudden cardiac death (SCD). AC is characterized by areas of fibro-fatty replacement of the myocardium of one or both ventricles, which can be characterized through cardiovascular magnetic resonance (CMR). Several mutations have been associated with the development of AC, most commonly in desmosomal genes. The relationship between the genotype and the disease phenotype (i.e., the extent and severity of myocardial disease and patient outcome) is unclear. Methods: We evaluated 280 consecutive patients evaluated in a single CMR laboratory over a 10-year timespan and diagnosed with AC according to the Padua criteria, based on a retrospective evaluation of the electronic health records. All these patients had undergone a genetic testing through Sanger sequencing or Next Generation Sequencing (after 2012). Pathogenic or likely pathogenic mutations and variants of unknown significance were considered. CMR scans performed at diagnosis were examined by an expert blinded to the results of genetic testing to retrieve the location and extent of the areas of fibro-fatty replacement and late gadolinium enhancement (LGE), biventricular volumes and function. Follow-up data were also retrieved. The primary endpoint was SCD or aborted SCD (following successful defibrillator discharge). The secondary endpoint included SCD or aborted SCD plus sustained or non-sustained ventricular tachycardia episodes. Results: Patients were more often males (67%), with a mean age of 48±16 years. Gene mutations related to cardiomyopathy were found in 123 patients, and 85 patients harbored mutations in desmosomal genes ( DSP, n=41; DSG2, n=16; PKP2, n=16; DSC2, n=6; JUP, n=6), while the other mutations were in genes including TMEM43, LMNA, SCN5A, MYH7, and RYR2 . Patients with mutations in desmosomal genes had more often LGE in the left ventricle (LV) than patients with other mutations or with no mutations detected (66% vs. 58% vs. 46%, respectively; p=0.025). Patients with mutations in the DSP gene had a greater LGE extent in terms of number of segments affected (p=0.011), or percent of the LV (p<0.001) compared with patients with other desmosomal mutations or no mutations. No differences between patients with desmosomal or non-desmosomal mutations or no mutations were found in terms of fibro-fatty replacement in the LV (51% vs. 32% vs. 48%; p=0.577), nor in terms of LGE presence or fibro-fatty replacement of the right ventricle (RV; data not shown). Median follow-up duration was 4.4 years (interquartile range 1.8-6.4); 22% of patients underwent defibrillator implantation. Primary endpoint events were recorded in 21 patients (7.5%), with 20 aborted SCD episodes. The secondary endpoint occurred in 58 patients (21%). At Cox regression analysis, the mutation status did not reach statistical significance as univariate predictor of the two endpoints, but LGE in the LV, LGE in ≥2 LV segments, or LGE >9% (considered one at the time) independently predicted both endpoints. Conclusions: In patients with AC, mutations in desmosomal genes are found in almost half of patients, and are associated with the presence and a larger extent of LGE in the LV. In turn, the presence and extent of LGE are independent predictor of SCD or aborted SCD.